In vitro biocompatibility analysis of functionalized poly(vinyl chloride)/layered double hydroxide nanocomposites - Singh, M.; Singh, R.K.; Singh, S.K.; Mahto, S.K.; Misra, N. (Royal Society of Chemistry, 2018)
The aim of this study was to examine the cytotoxicity and biocompatibility of functionalized poly(vinyl chloride) (PVC)/layered double hydroxide (LDH) nanocomposites. The biocompatibility of the LDH-based nanocomposites of thiosulphate PVC (TS-PVC), thiourea PVC (TU-PVC) and sulphite PVC (S-PVC) was assessed via haemolysis and thrombogenicity tests followed by the analysis of cellular adhesion and proliferation. The MTT assay was performed on cells in direct contact with the polymeric nanocomposites to evaluate the side effects of the biomaterials. The cellular morphology of mouse mesenchymal stem cells was also analyzed after incubation with direct contact with the functionalized polymer nanocomposites for different time periods. Although the results of the haemolysis test displayed a positive influence of LDH on the functionalized PVC compared to the neat PVC, the thrombogenic property was observed to be notably decreased, which indicated improved blood compatibility. The resulting LDH samples were also studied for their performance via fluorescence imaging of cells after incubation with the materials. The LDH-based polymers exhibited an excellent level of cytocompatibility, which validates their use as biomaterials. PVC-TU/LDH-2 and PVC-S-2 were found to be notably less cytotoxic for the tested cell type. Also, the cells were found to adhere better to the entire PVC-S/LDH nanocomposite surface. The cytotoxicity test also revealed that the PVC-TU/LDH and PVC-S/LDH nanocomposites exhibited similar responses. The fluorescence-based image analysis showed that cells were spread much more on the polymer surface containing a higher LDH weight percentage. Overall, this study provides a benchmark for the biocompatibility properties of PVC/LDH nanocomposites, which may be useful for numerous applications in the biomedical and related areas. © The Royal Society of Chemistry.
Keywords: biocompatibility; poly(vinyl chloride); hydroxide nanocomposites